2016
DOI: 10.1017/s1049023x16001114
|View full text |Cite
|
Sign up to set email alerts
|

Why do Emergency Medical Services (EMS) Professionals Leave EMS?

Abstract: Objective: The objective was to determine why Emergency Medical Technician (EMT)-Basics and Paramedics leave the Emergency Medical Services (EMS) workforce. Methods: Data were collected through annual surveys of nationally registered EMT-Basics and Paramedics from 1999 to 2008. Survey items dealing with satisfaction with the EMS profession, likelihood of leaving the profession, and likelihood of leaving their EMS job were assessed for both EMT-Basics and Paramedics, along with reasons for leaving the professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…The most significant reasons for quitting the paramedic job cited by the interviewees in the present study are similar to those mentioned in previous studies in other countries [27, 28]. Moreover, the reasons cited in the qualitative interviews were consistent with those listed in the online survey.…”
Section: Discussionsupporting
confidence: 89%
“…The most significant reasons for quitting the paramedic job cited by the interviewees in the present study are similar to those mentioned in previous studies in other countries [27, 28]. Moreover, the reasons cited in the qualitative interviews were consistent with those listed in the online survey.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, they experience high levels of stress and suffer from chronic stress. Studies showed that 22% of EMS providers deal with stress-related complications [3,4] such as anxiety, irritability, social isolation, sleep disorder [5][6][7][8], job dissatisfaction, burnout [9][10][11], workplace incivility, leaving the profession, suicide [12][13][14] post-traumatic stress disorder, risk behaviors, psychological problems, and depression, and are more likely to commit medical errors [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In prior work from the Committee on Accreditation of Educational Programs for the EMS Professions and the National Association of EMS Educators, surveys of EMS educators identified concerns early in the pandemic consistent with many of the top 8 research priorities identified by the panel 11,12 . Access to education and the ability to complete continuing education were recognized as challenges affecting recruitment and retention in EMS, even before the COVID‐19 pandemic 23–25 . Many EMS education programs reported varying levels of continued operation, 11–13 which potentially limits access to initial EMS education.…”
Section: Discussionmentioning
confidence: 99%